Development of Metal Organic Framework Filled Pdms/Pi Composite Membranes for Biobutanol Recovery - Romero-Figueroa, J (Springer New York LLC, 2019)
Butanol is a second generation biofuel with high potential to replace fossil fuels in the future. The main drawbacks in biobutanol production are the low yields of operation and high cost of separation. In this study, n-butanol recovery from its aqueous solutions was carried out by pervaporation as an alternative separation process using polyimide supported polydimethylsiloxane membranes, which were especially prepared for this purpose. To enhance the separation efficiency of the membrane, metal organic framework fillers of MOF-199 were included in its structure. Several combinations of polyimide supported PDMS active layered membranes were prepared with the fillers in each layer of the membrane, in both layers of membrane and membranes without fillers. Thus, the effect of the fillers on the separation performance was investigated. It was found that the inclusion of MOF-199 enhances the membrane performance; meanwhile, the support layer also contributes to mass transfer of n-butanol. Furthermore, the effect of the process parameters on the pervaporation performance was investigated. Results of pervaporation tests indicate that the developed membranes have a good potential for n-butanol recovery from aqueous mixtures. © 2019, The Korean Institute of Chemical Engineering (KIChE).